Urgensi Pembentukan Kampung Pengawasan Badan Pengawas Pemilu terhadap Pengawasan Partisipatif pada Provinsi Kalimantan Tengah dalam Menghadapi Pemilihan Kepala Daerah Serentak Tahun 2024 - Gina Amalia; Nadila Nadila; Sonia Sonia; Aris Sunandar Suradilaga (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
The participatory oversight program includes the establishment of oversight villages in Central Kalimantan to involve the community in overseeing the Simultaneous Regional Head Elections in 2024.The urgency of establishing oversight villages for community participatory oversight is to increase participation, strengthen the oversight function of Bawaslu, prevent violations, and enhance transparency and accountability.The challenges in the implementation of oversight villages include limited human resources, lack of public understanding, geographical and infrastructural challenges, budget constraints, as well as practical politics and local interests.Strategic steps to address these challenges include stakeholder collaboration, intensification of training, infrastructure improvement, and the utilization of technology.Through oversight villages, the community is expected to actively participate in monitoring the regional elections to achieve clean, transparent, and accountable elections.